1996
DOI: 10.1002/elps.1150171017
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of glycated hemoglobins in human adult blood by capillary isoelectric focusing

Abstract: A precise and reproducible method for assessment of glycated hemoglobin in human adult red blood cells is reported, based on capillary isoelectric focusing (IEF). In order to obtain baseline resolution between adult hemoglobin (Hb A) and its glycated form (Hb A1c), two species which differ by minute delta pI values, < 0.03 pH units, the following procedure was adopted: the focusing mixture consisted of 5% Ampholine, pH 6-8, 0.5% Pharmalyte, pH 3-10, 3% short-chain liquid polyacrylamide and an equimolar mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…A case in point is offered in Fig. 4, which is at the basis of the good separations of glycated Hbs, as well as umbilical cord Hbs reported in [53,54]. As one can see, a pH 6-8 interval (excellent for separation of just about all Hb species) is not quite linear, as assessed by experimentally monitoring the pH course.…”
Section: Pitfalls and Fata Morgana'smentioning
confidence: 94%
See 1 more Smart Citation
“…A case in point is offered in Fig. 4, which is at the basis of the good separations of glycated Hbs, as well as umbilical cord Hbs reported in [53,54]. As one can see, a pH 6-8 interval (excellent for separation of just about all Hb species) is not quite linear, as assessed by experimentally monitoring the pH course.…”
Section: Pitfalls and Fata Morgana'smentioning
confidence: 94%
“…We recommend to abolish all non-buffering ions in a cIEF system, which means using also weak electrolytes at the electrodic compartments; e.g. instead of phosphoric acid, one can adopt acetic acid, or zwitterions, such as free Asp or Glu or imino diacetic acids, as anolytes; conversely, as catholytes, one should use free Lys, Arg or Tris, ethanolamine, and the like, in lieu of the highly corrosive NaOH, unless one uses highly hydrolytically stable N-substituted acrylamides [53,54].…”
Section: Salts and Solubilizersmentioning
confidence: 99%
“…However, acidic proteins at the far end of the capillary are mobilized with lower eficiency and may exhibit zone broadening or be undetected. Conti et al [4] reported that use of high concentrations (100 mM) of sodium chloride in cathodic mobilization resulted in deterioration of the capillary coating which they attributed to the formation of strong alkaline boundaries. Neutral salts other than sodium chloride can be used for mobilization.…”
Section: Chemical Mobilizationmentioning
confidence: 98%
“…Conti el al. [4] decreased the slope of the pH gradient in the region around pH 7 in order to resolve glycated hemoglobins, including Hb A,,, by incorporating a mixture of 0.33 M 6-aminocaproic acid and 0.33 M 0-aianine to a mixture of ampholytes (Ampholine 6-8, and Pharmalyte 3-10). A limitation of on-tube absorbance detection is the potential for background interference from the ampholytes.…”
Section: Ampholyte Compositionmentioning
confidence: 99%
“…The separation of Hemoglobins Hb A from Hb A 1c may be an classic example [33,34] where the separations with pI < 0.03 pH units were demonstrated. They were separated by CIEF [35,36] using focusing mixture consisted of commercial carrier ampholytes, short-chain liquid polyacrylamide and an equimolar mixture of two electrolytes [35]. The wide pH gradient course is traced by several pI markers [33,34].…”
Section: Introductionmentioning
confidence: 99%